Conceptualising the separation from an abusive partner as a multifactorial, non-linear, dynamic process: A parallel with Newton’s laws of motion - Di Basilio, Daniela; Guglielmucci, Fanny; Livanou, Maria (Frontiers in Psychology, 2022)
The present study focused on the dynamics and factors underpinning domestic abuse (DA) survivors’ decisions to end the abusive relationship. The experiences and opinions of 12 female DA survivors and 18 support workers were examined through in-depth, one-to-one, semi-structured interviews. Hybrid thematic analysis was conducted to retrieve semantic themes and explore relationships among the themes identified and the differences in survivors' and professionals' narratives of the separation process. The findings highlighted that separation decisions derived from the joint action of two sets of factors, the ‘promoters’ and the 'accelerators’. Whilst the ‘promoters’ are factors leading to the separation from the abuser over time, the ‘accelerators’ bear a stronger and more direct connection with survivors’ decision to end the abusive relationship. Despite their differences, both these factors acted as propelling forces, leading survivors to actively pursue the separation from the perpetrator. To portray the dynamic links among these factors, we propose a conceptualisation drawn from Newton’s laws of motion. Our findings also highlighted important differences in the views of survivors and support workers, as the former conceived themselves as proactive in ending the abuse, whereas the latter described the leaving process as mainly led by authorities and services supporting survivors. This study has potential implications for research, policy and clinical practice, as it suggests that far from being a linear sequence of multiple stages, leaving an abusive relationship results from a complex interplay of factors that facilitate (‘promoters’) or drastically accelerate (‘accelerators’) the separation process. We argue that future research should aim at improving our current understanding of the subjective and situational factors that can act as ‘accelerators’ or ‘promoters’ for women’s leaving decisions. Moreover, clinicians and policymakers should invest in creating interventions that aid victims to recognise and leverage promoters and accelerators, thus increasing their readiness to end the abuse.